Nahum's Shaking Cypresses - Cook, Gregory (Bulletin for biblical research, 2016)
The final two words of Nah 2:4 (2:3 NRSV) seem to suggest shaking trees, but scholars either emend MT or interpret the clause metaphorically. The literature deems the possibility of still-standing trees as ill-fitted to the context of Nah 2. This article proposes that the words והברשים הועלו do indeed refer to standing cypress trees. In Nah 2:4, the Ninevites see distant trees quaking as the besiegers chop them down to build siege engines. Sennacherib (reigned 705–681 B.C.) had created forests around Nineveh during his expansion of the city. These forests included transplanted cypresses. Nahum prophesied that these trees would be turned against the city by invading forces.